Indonesia in ASEAN: Foreign Policy and Regionalism by Dewi Fortuna Anwar. Regional Strategic Studies Programme, Institute of Southeast Asian Studies, n.d. xiii + 335pp. (American Journal of Islam and Society, 1997)
This book analyzes Indonesia's political and economic commitment toASEAN. ASEAN compries six Southeast Asian countries: Brunei, Indonesia,Malaysia, the Philippines, Singapore, and Thailand. To clarify that commitment,Anwar makes a deliberate attempt to investigate ASEAN's underlying assumptions.Specifically, the organization is intended to promote harmony and peacein the region, given that ASEAN countries are relatively more politically stableand economically developed compared to the nearby Indochinese states. Inadrution, ASEAN has been perceived as attempting to manage regional orderagrunst nonregional powers such as Chma while strengthening Western ties. Theauthor examines these assumptions on the premise that ASEAN is mainly a distinctivevehicle of Indonesian foreign policy. To do so, he follows Weinstein'sapproach, which I based on the uses of foreign policy, that is, his analysis does not adopt a common theory. Thus, he unintentionally goes back and forth to verify what seems to be the main theme of the book: how Indonesia sought regionalleadership through ASEAN to achieve its main goals of foreign policy ...